2010
DOI: 10.1097/bot.0b013e3181d35c29
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do Locked Screws Add to the Fixation of “Hybrid” Plate Constructs in Osteoporotic Bone?

Abstract: Biomechanical level 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…The same conclusion was reached in veterinary applications for radius, ulna and tibia fractures in dogs and cats [14,24]. Others, however, recommend at least 3 screws per segment, especially if dealing with osteoporotic bone [5,25,26]. Hak et al were unable to show a mechanical benefit from the addition of a third locking screw per segment in the manner tested in freshfrozen human cadaveric humeri [21].…”
Section: Discussionmentioning
confidence: 67%
“…The same conclusion was reached in veterinary applications for radius, ulna and tibia fractures in dogs and cats [14,24]. Others, however, recommend at least 3 screws per segment, especially if dealing with osteoporotic bone [5,25,26]. Hak et al were unable to show a mechanical benefit from the addition of a third locking screw per segment in the manner tested in freshfrozen human cadaveric humeri [21].…”
Section: Discussionmentioning
confidence: 67%
“…16 Biomechanical studies have consistently shown the advantage of locking-plate technology over non-locked fixation in osteoporosis. 17,18 There has been an increase in the use of locked plates despite their use in osteoporotic ankle fractures not yet having been fully evaluated and it is uncertain how this technique will translate into clinical benefit. A recent retrospective review from the Netherlands showed a significant increase in wound complication rates with locking plates compared with third tubular plates in distal fibular fractures; 5.5% with the conventional plates and 17.5% in the locking plate group.…”
Section: Operative Treatmentmentioning
confidence: 98%
“…Blocked plates support higher flexion loads and torsions than conventional plates, resulting in higher stress over the implant. Due to this fact, several authors propose the use of conventional cortical screws close the fracture focus, in particular when working area is smaller, what seems to be ideal for fractures with multifragment pattern 10,12,13 . This technical detail reduces rigidity of the construction compared to the use of blocked screws 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to this fact, several authors propose the use of conventional cortical screws close the fracture focus, in particular when working area is smaller, what seems to be ideal for fractures with multifragment pattern 10,12,13 . This technical detail reduces rigidity of the construction compared to the use of blocked screws 13 . In the present study, although it was not the choice of most participants, the authors options for the different presented situation would be the use of a bigger working area for type AO 32-A3 ("option 1") and a smaller working area for type AO 32-C3 ("option 3").…”
Section: Discussionmentioning
confidence: 99%